Fomento para a produção de soja na região do Matopiba via fundo de investimento externo: estudo de caso da rentabilidade esperada para os produtores e investidores - Leal, Washington Moura (Universidade do Vale do Rio dos Sinos, 2017)
The present study has as objective determinate and analyze the expected profitability of soybean’s producers and the investment funds that finances the production of soy on the region of MATOPIBA. It is about a study of financial’s case of a soy’s plantation project that involves buying lands, machines and covering the costs of all the expenses of the rural properties by means of a fund, that, in return, receives from the producers 80% of all the production during the contract’s period that is 8 years. The investment refers to a plantation of 843.621,32 hectares of soybean, among the states of Maranhão, Tocantins, Piauí and Bahia a region denominated as MATOPIBA, where includes 25 producers, according to the following status: 14 in production, 5 in negotiation and 6 being expected. The production of soy bags will occurs in the first two years 45 bags per ha, in the third year 55 bags, in the fourth, fifth and sixth year 60 bags and in the latest years 65 bags. For the present study, the analysis of bags per hectare was carried out. In the analysis’s results can be checked that the return of the Investments Fund is average 2,29 soybean bags per planted hectare at the end of an eight years period, while the producer has a net income on average 6,52 bags per hectare also in a period of eight years. The investors of the Investments Fund have a remuneration of 6% of interest per annum, cumulative until the end of the project’s period that is eight years, which represents a return of 28,68% in average.
Keywords: Rentabilidade; Retorno do investimento; Custo de produção; MATOPIBA; Profitability; Investment’s return; Production cost; MATOPIBA; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis